Flexibility of deployment: challenges and policy options for retaining health workers during crisis in Zimbabwe - Wilson Mashange; Tim Martineau; Pamela Chandiwana; Yotamu Chirwa; Vongai Mildred Pepukai; Shungu Munyati; Alvaro Alonso-Garbayo (BMC, 2019)
Abstract Background Zimbabwe experienced a socio-economic crisis from 1997 to 2008 which heavily impacted all sectors. In this context, human resource managers were confronted with the challenge of health worker shortage in rural areas and, at the same time, had to operate under a highly centralised, government-centred system which defined health worker deployment policies. This study examines the implementation of deployment policies in Zimbabwe before, during and after the crisis in order to analyse how the official policy environment evolved over time, present the actual practices used by managers to cope with the crisis and draw lessons. 'Deployment' here was considered to include all the human resource management functions for getting staff into posts and managing subsequent movements: recruitment, bonding, transfer and secondment. The study contributes to address the existing paucity of evidence on flexibility on implementation of policies in crisis/conflict settings. Methods This retrospective study investigates deployment policies in government and faith-based organisation health facilities in Zimbabwe before, during and after the crisis. A document review was done to understand the policy environment. In-depth interviews with key informant including policy makers, managers and health workers in selected facilities in three mainly rural districts in the Midlands province were conducted. Data generated was analysed using a framework approach. Results Before the crisis, health workers were allowed to look for jobs on their own, while during the crisis, they were given three choices and after the crisis the preference choice was withdrawn. The government froze recruitment in all sectors during the crisis which severely affected health workers' deployment. In practice, the implementation of the deployment policies was relatively flexible. In some cases, health workers were transferred to retain them, the recruitment freeze was temporarily lifted to fill priority vacancies, the length of the bonding period was reduced including relaxation of withholding certificates, and managers used secondment to relocate workers to priority areas. Conclusion Flexibility in the implementation of deployment policies during crises may increase the resilience of the system and contribute to the retention of health workers. This, in turn, may assist in ensuring coverage of health services in hard-to-reach areas.